The Labatory of the Future - Catalogue of the 18th International Architecture Exhibition : Volume 1 - Exhibition - Lokko, Lesley, ....-; Biennale Architettura (Venetië : Biennale Architettura 2023, 2023)
The 18th International Architecture Exhibition, in Venice from May 20th to November 26th, 2023, is entitled The Laboratory of the Future. Conceived as “a kind of workshop, a laboratory where architects and practitioners across an expanded field of creative disciplines draw out examples from their contemporary practices that chart a path for the audience — participants and visitors alike — to weave through, imagining for themselves what the future can hold” (Lesley Lokko). The Catalogue of the Biennale Architettura 2023 is divided into two volumes and follows the organisation of the Exhibition, accompanying visitors and architecture enthusiasts through the exhibition spaces of the Arsenale and the Giardini, and towards the other projects showing in various locations in the city of Venice and in Forte Marghera, in Mestre.
Volume I of the Catalogue, divided into different sections, opens with statements from the President of La Biennale di Venezia, Roberto Cicutto, and the Artistic Director of the Architecture Department, Lesley Lokko. One section is dedicated to the events of Carnival, a cycle of lectures, debates, panel discussions and performances that explore the themes of the 18th International Architecture Exhibition, followed by a section dedicated to Special Projects. The Volume then dedicates two sections to the International Exhibition curated by Lesley Lokko, respectively titled Force Majeure and Dangerous Liasons. Each project on display in the Exhibition is accompanied by a critical text and a rich iconography that completes the Participants’ work. A further section is dedicated to the first edition of the Biennale College Architettura, which will hold its workshop from June 25th to July 22nd, 2023, in Venice. Threaded throughout are a series of essays developing the themes of the Exhibition and a detailed record of the works on display.
Keywords: Architectuur; Kunst